Financial Crisis Cyclicality in Europe under the US Financial Disturbances’ Impact. A Logical Framework - Cristina Drumea (Ovidius University Annals: Economic Sciences Series, 2023)
The cyclicality concept of the economic and financial crisis is well known and recurrently experienced by the Western world economies. Various triggers could be depicted for each of the crisis episodes, but some remain constant in the post-factum analyses. While political events (war/territorial disputes, energy crisis, fiscal and monetary policies) or calamities (pandemic) cannot be either anticipated or influenced, their effects, which shape each crisis (inflation rate, cost of living, supply shortages, bankruptcies) should be possible to anticipate, in order to mitigate crisis’ effects on population and businesses. Looking for patterns of the last century crisis is the obvious line of defense so that early signs are captured and acted on for future occurrences. Despite global indicators being monitored and triggers being put in place, the cyclic crisis pattern is one that could not be broken.